2014
DOI: 10.3109/1354750x.2014.885084
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of NAD(P)H:quinone oxidoreductase 1 activity and increase of ROS production by NADPH oxidases are early biomarkers in doxorubicin cardiotoxicity

Abstract: Context. Doxorubicin cardiotoxicity displays a complex and multifactorial progression.Objective. Identify early biochemical mechanisms leading to a sustained imbalance of cellular bioenergetics.Methods. Measurements of the temporal evolution of selected biochemical markers after treatment of rats with doxorubicin (20 mg/kg body weight).Results. Doxorubicin treatment increased lipid oxidation, catalase activity and production of H2O2 by Nox-NADPH oxidases, and down-regulated NAD(P)H:quinone oxidoreductase-1 pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…In particular, depletion of ROS reverses the EndMT process in HAECs [44]. LIPUS has been documented to reduce ROS accumulation via protein kinase A-mediated inhibition of NAD(P)H oxidases [45]. In agreement with these findings, we demonstrated here that LIPUS suppressed EndMT primarily via its anti-oxidant action, which represents the first to identify the cytoprotective effects of LIPUS against oxidative stress-induced arterial endothelium injuries.…”
Section: Discussionsupporting
confidence: 79%
“…In particular, depletion of ROS reverses the EndMT process in HAECs [44]. LIPUS has been documented to reduce ROS accumulation via protein kinase A-mediated inhibition of NAD(P)H oxidases [45]. In agreement with these findings, we demonstrated here that LIPUS suppressed EndMT primarily via its anti-oxidant action, which represents the first to identify the cytoprotective effects of LIPUS against oxidative stress-induced arterial endothelium injuries.…”
Section: Discussionsupporting
confidence: 79%
“…Peroxidase activity was measured by the Amplex Red assay as used in previous works by our laboratory . In a previous work, we found that epicatechin, quercetin, kaempferol, apigenin, and naringenin do not interfere with the Amplex Red assay and have no significant effect on the response to H 2 O 2 as assessed with calibration curves in the absence and in the presence of the flavonoids .…”
Section: Resultsmentioning
confidence: 99%
“…Cardiolipin‐induced peroxidase activity of Cyt c was measured by the Amplex Red assay adapting the procedures followed by other authors and in previous works from our laboratory . Cyt c (1 μM) was mixed with lipid vesicles (PC or PC/CL SUV) at a concentration of 100 μM, for 5 min at 37°C, and oxidation of Amplex Red (5 μM) to the fluorescent product resorufin was initiated with 25 μM H 2 O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been recognized that DOX-induced cardiotoxicity is also characterized by excessive intracellular ROS production [ 25 ]. ROS mediates cell apoptosis via multiple mechanisms such as impairing membrane integrity and causing mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%